Feasibility Assessment of Bifacial Rooftop Photovoltaic Systems in the State of Gujarat in India - Desai, Alpesh; Mukhopadhyay, Indrajit; Ray, Abhijit (Frontiers in Energy Research, 2022)
Bifacial solar photovoltaic (PV) modules are one of the recent interventions in the widespread commercial deployment of solar energy. This study intends to analyze the adoption of bifacial solar panels in rooftop PV systems to enhance energy generation as compared to their mono-facial counterparts. The technical and economic advantages of a typical 5-kW single-phase solar rooftop photovoltaic system using bifacial Si-modules are presented and compared with those using traditional polycrystalline Si (poly c-Si) modules in the urban location of the state of Gujarat in India. This methodology allows one to find optimal performance under the same irradiation and load conditions. As the majority of terraces in this location have a surface of white or gray tiles, which have a high albedo factor, bifacial modules generate more than 10% excess energy as compared to the poly c-Si systems. Although bifacial modules have an initial cost higher than the polycrystalline counterparts, the cost of their balance of system and space is reduced by 2 to 13%, respectively. Analysis shows that a 5kW bifacial technology can generate an excess of 13 MWh as compared to the traditional poly-Si over a period of 25 years. Finally, it is seen that an optimized bifacial system that is tilted between 15 and 20° will reduce the levelized cost of electricity (LCOE) by 5.5% as compared to the traditional poly c-Si system.